Peripheral blood MR1 tetramer‐positive mucosal‐associated invariant T‐cell function is modulated by mammalian target of rapamycin complex 1 in patients with active tuberculosis - Zhou, Chao‐Ying; Yang, Ya‐Long; Han, Zhen‐Yu; Chen, Yao‐Xin; Liu, Hong‐Lin; Fan, Ke; Li, Ming‐Chong; Tu, Si‐Hang; Wen, Qian; Zhou, Xin‐Ying; Ma, Li (Immunology, 2024)
Tuberculosis (TB) is still an urgent global public health problem. Notably, mucosal‐associated invariant T (MAIT) cells play an important role in early anti‐TB immune response. Targeted control of them may be an effective method to improve vaccine efficacy and TB treatment. However, the biology and signal regulation mechanisms of MAIT cells in TB patients are still poorly understood. Previous studies have been limited by the lack of reagents to specifically identify MAIT cells. In addition, the use of alternative markers may subsume non‐MAIT cell into MAIT cell populations. In this study, the human MR1 tetramer which can specifically identify MAIT cells was used to further explore the effect and mechanism of MAIT cells in anti‐TB immune response. Our results showed that the tetramer+ MAIT cells in peripheral blood of TB patients were mainly CD8+ or CD4−CD8− cells, and very few were CD4+ cells. After BCG infecting autologous antigen‐presenting cells, MAIT cells in patients produced significantly higher levels of cytokines, lysis and proliferation compared with healthy controls. After suppression of mTORC1 by the mTORC1‐specific inhibitor rapamycin, the immune response of MAIT cells in patients was significantly reduced. This study demonstrates that peripheral blood tetramer+ MAIT cells from TB patients have significant anti‐TB immune effect, which is regulated by mTORC1. This could provide ideas and potential therapeutic targets for the development of novel anti‐TB immunotherapy. Peripheral blood tetramer+ MAIT cells from TB patients have significant anti‐TB immune effect. After suppression of mTORC1 by rapamycin, the immune response of peripheral blood tetramer+ MAIT cells in TB patients was significantly reduced. The anti‐TB immune effect of peripheral blood tetramer+ MAIT cells in TB patients is regulated by mTORC1.